THE ASSESSMENT OF THE FILLING STATIONS IMPACT ON THE ENVIRONMENT - Cherniak, Larysa; Radomska, Margaryta; Madzhd, Svitlana; Hryb, Alina; Pavliukh, Lesia (Proceedings of National Aviation University (archive), 2020)
The work is devoted to the environmental impacts of the filling station. Authors have shown that of pollutants, emitted from the filling station, are toxic substances, which often cause irreversible damage to the organism, including functional and system disorders, acute and chronic non-specific and specific effects. The analysis of soil acidity at typical gas stations was carried out, as well as sumpling in the area of filling stations operation. For determination the soils acidity samples were taken at 8 filling stations. Most of the analyzed sites have a soil reaction close to neutral, indicating the presence of pollution with petrochemicals. The drilling results show that there is a serious factor of soil pollution in the operation of filling station. As a result of the analysis of possible impacts at the filling station, recommendations were made for reducing their negative environmental impacts. The necessity of prevention of negative impacts of filling station was substantiated.